PENGARUH PENEMPATAN KERJA, PELATIHAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. FLORA WAHANA TIRTA PKS DI KEBUN DURIAN KECAMATAN GUNUNG SAHILAN - Riko, Pratama; Susi, Hendriani; Raden, Ganarsih Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to determine and analyze the effect of work placement, training and compensation simultaneously and partially on job satisfaction of employees of PT. Flora Wahanatirta PKS in Kebun Durian, Gunung Sahilan Sub-District. The population in this study were employees of PT. Flora Wahanatirta PKS in Kebun Durian, Gunung Sahilan Sub-district, totaling 103 people. The sample used was 51 respondents. The sampling technique used is Probability Sampling with the type of propotionate stratified random sampling. Analysis of the data used is statistical analysis using the SPSS 17.0 program. The results of the analysis with the SPSS program, found that the relationship between work placement (X1), training (X2) and compensation (X3) with employee job satisfaction (Y) has a very strong relationship level that is equal to 0.805. Simultaneously, the variable work placement (X1), training (X2) and compensation (X3) affect employee job satisfaction (Y). Partially, the work placement variable (X1) has no effect on employee job satisfaction (Y), while the training variable (X1) and compensation (X2) have a positive and significant effect on employee job satisfaction (Y).Keywords: work placement, training, compensation, employee job satisfaction